MULTIMEDIA TECHNOLOGIES AS A MEANS OF MOTIVATING STUDENTS IN THE PROCESS OF TEACHING FOREIGN LANGUAGES - Tashpulatova Nargiza Samaritdinovna; Nurullaeva Khadicha (Galaxy International Interdisciplinary Research Journal, 2022)
The article is devoted to the role of multimedia technologies in the foreign language teaching. The authors of the article consider them as a means of students’ motivation. It is said, multimedia technologies help to develop communicative competence that is an essential part in the foreign language acquisition. Also, it is noted, computer technologies make the education process more efficient and the authors state that modern technologies usage is effective at all stages of language teaching and with all different groups of students.